Dampak Covid-19 Terhadap Industri Pariwisata Di Manggarai Barat - Irna Karina J.Kaban; Ida Ayu Rostini (Jurnal Sains Terapan Pariwisata, 2020)
Since then the Indonesian government has started to issue policies to reduce the spread of the covid-19 virus by implementing large-scale societal restrictions that have resulted in the closure of schools, workplaces and crowded places including tourist spots and restrictions on international and national flights. This has had a huge impact on the development of the tourism industry including the West Manggarai tourism industry which is recognized as the Komodo National Park. Therefore, it is necessary in order to conduct a scientific study to determine how to dig the influence of Covid-19 is on the Tourism Industry in West Manggarai. The results of this study are invited to become the basis for policy making to deal with the impact of Covid-19 appropriately. A study of the impact of covid-19 on tourism in West Manggarai was carried out using primary and secondary data. Primary data were generated using an online questionnaire distributed to tourism actors in the period 18-31 May 2020. The selection of respondents used snowball techniques (snowball sampling) and collected 129 respondents. Ancillary data collection through literature reviews was also carried out to fruitful insights on various policies to cope with the impact of covid-19. Data analysis used qualitative and quantitative approaches. Primary data were analyzed by looking at the similarities and differences. The results of the study concluded that Covid-19 triggered a potential loss of revenue from the tourism sector of more than 5 billion throughout 2020. Most respondents did not have adequate resources related to crisis management. Several recommendations are needed to decrease the influence of covid-19 on the tourism industry including long-term, short-term recommendations and recommendations for destination marketing.